Experimental Verification and Evolutionary Origin of 5′-UTR Polyadenylation Sites in Arabidopsis thaliana - Zhu, Yingdong; Vaughn, Jack C. (Frontiers in Plant Science, 2018)
Messenger RNA (mRNA) polyadenylation is an indispensable step during post-transcriptional pre-mRNA processing for most genes in eukaryotes. The usage of one poly(A) site over another is known as alternative polyadenylation (APA). APA has been implicated in gene expression regulation through its role of selecting the ends of a transcript. Recent studies of polyadenylation profiles in the Arabidopsis database unexpectedly predicted that a portion of the poly(A) sites are located in the 5’-UTR, which remains to be experimentally verified. We selected 16 genes from a dataset of 744, based on criteria designed to minimize problems in interpretation. Here, we experimentally verify 5’-UTR-APA in Arabidopsis for 10 of the 16 selected genes, and show for the first time existence of independent polyadenylated 5’-UTR transcripts, arising due to alternative polyadenylation. We used 3’-RACE and sequencing to validate poly(A) sites and northern blot to show that the observed short upstream transcripts do not arise from the 3’-end of a previously unrecognized convergent gene. Evidence is reported showing that two of the independent upstream open reading frame (uORF) transcripts studied, one containing a complex dual uORF, very likely arose by exon shuffling following duplication of the 5’-end from the downstream major open reading frame (mORF). Finally, results are presented to show that the uORF in this gene may encode two short functional proteins, based on observation of amino acid sequence conservation encoded by the dual uORFs.